2015
DOI: 10.3109/14756366.2015.1021252
|View full text |Cite
|
Sign up to set email alerts
|

Unifi nootropics from the lab to the web: a story of academic (and industrial) shortcomings

Abstract: This paper is a review of the work of my former academic group of research in the past 15 years, in the field of cognition enhancers (also called nootropics) that identified two very potent molecules: Unifiram and Sunifiram that for a variety of reasons were not protected by a patent. Some 12 years after their disclosure (2000) I casually found that on the web, there were dozens of sites offering Unifiram and Sunifiram as drugs that improve cognition in healthy individuals even if only few preclinical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Sunifiram (DM235) is a novel potent nootropic drug developed by Gualtieri research group in 2000 and is considered as new class of nootropic agents. 23 Sunifiram and related compound Unifram (DM232) ( Figure 2 ) are able to enhance cognitive function four-fold greater than Piracetam in behavioural experiments such as Morris water maze task. 24 These drugs can be helpful in treatment of neurodegenerative disorder like Alzheimer’s, Parkinson’s, multiple sclerosis, schizophrenia, and attention-deficit hyperactivity disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Sunifiram (DM235) is a novel potent nootropic drug developed by Gualtieri research group in 2000 and is considered as new class of nootropic agents. 23 Sunifiram and related compound Unifram (DM232) ( Figure 2 ) are able to enhance cognitive function four-fold greater than Piracetam in behavioural experiments such as Morris water maze task. 24 These drugs can be helpful in treatment of neurodegenerative disorder like Alzheimer’s, Parkinson’s, multiple sclerosis, schizophrenia, and attention-deficit hyperactivity disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Out of some 101 designer benzodiazepine compounds, Catalani et al [75] recently carried out a range of docking/in silico studies and identified a total of 12 molecules, including fluadinazolam, pyclazolam, pynazolam, and tofisopam, showing potential binding levels consistent with being GABA-A receptor α5 selective inverse agonists. Gualtieri [80] described how, in the 1980s, he had identified two potential, not patent protected, not toxicologically-assessed, CEs (e.g. unifiram [DM 232] and sunifiram [DM 235]), which are now popular on the web.…”
Section: Racetams Including Piracetammentioning
confidence: 99%
“…These adulterated supplements could harbour severe risks for the oblivious consumer, in fact, one case with a lethal outcome has been reported in the scientific literature, where a natural health supplement contained a product termed 1,3-dimethylamylamine [3]. Furthermore, some research chemicals that did not undergo clinical testing or products for which only limited knowledge of their longterm toxicity is available, are sold via the internet as food supplements [4][5][6][7][8][9][10][11]. Therefore, several actions are on-going worldwide to protect the public from these malignant activities.…”
mentioning
confidence: 99%